1988
DOI: 10.1002/bms.1200160120
|View full text |Cite
|
Sign up to set email alerts
|

In-depth limitation of the Lamma 500 for thein situ localization of organic compounds in biological embedded tissue samples

Abstract: The objective of this study was exploration of the potential, offered by the laser microprobe mass spectrometer (LAMMA), for the in situ localization of organic targets in embedded tissues by means of structurally relevant ions. A series of model systems was designed to evaluate stepwise the analytical problems involved. A preliminary screening pointed to the position of the target in comparison to the actual sample surface as a determining parameter. Refined simulations were carried out with sandwich samples,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1989
1989
2006
2006

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…There is substantial evidence that the surface components are ionized preferentially and that the underlying layers are only vaporized but do not contribute significantly to the detected signals. It was shown that the detected ions from organic compounds in transmission TOF LMMS issued from the upper 10-50nm when a 1-,um section was perforated (163). The situation is less clear for elemental and inorganic cluster ions in TOF LMMS.…”
Section: Techniquesmentioning
confidence: 97%
“…There is substantial evidence that the surface components are ionized preferentially and that the underlying layers are only vaporized but do not contribute significantly to the detected signals. It was shown that the detected ions from organic compounds in transmission TOF LMMS issued from the upper 10-50nm when a 1-,um section was perforated (163). The situation is less clear for elemental and inorganic cluster ions in TOF LMMS.…”
Section: Techniquesmentioning
confidence: 97%
“…1437 Applied Spectroscopy in Material Science (1991) / 139 laser shot, thus giving a very broad temporal distribution of desorbed species [21] that limits the practical resolving power of a TOE mass spectrometer to a few thousand in the best cases.…”
Section: Mass Resolving Powermentioning
confidence: 99%
“…30,31 Application of a focused UV laser pulse at a power density of 10 6 -10 10 W cm -2 allowed TOF LMMS to generate atomic and structural ions from a local microvolume in the sample with a lateral resolution in the range of 0.5-2 µm and an information depth of at least 10-50 nm. 32,33 To overcome the lack of mass resolution in the initially commercialized TOF LMMS instruments, several Fourier transform ion cyclotron resonance (FTICR) mass spectrometers were adapted to laser microprobe analysis. [34][35][36][37][38][39][40] The instruments with external ion source featured a mass resolution as high as 4 000 000 (for m/z < 100) or at least 100 000 (up to m/z 2000) and a mass accuracy within 10 -6 of the mass-over-charge (m/z) ratio.…”
Section: Fourier Transform Ion Cyclotron Resonance Laser Microprobe M...mentioning
confidence: 99%
“…Introduced in the 1980s, LMMS with a time-of-flight (TOF) analyzer has been a competitor to S-SIMS for the local analysis of solids. , Application of a focused UV laser pulse at a power density of 10 6 −10 10 W cm -2 allowed TOF LMMS to generate atomic and structural ions from a local microvolume in the sample with a lateral resolution in the range of 0.5−2 μm and an information depth of at least 10−50 nm. , To overcome the lack of mass resolution in the initially commercialized TOF LMMS instruments, several Fourier transform ion cyclotron resonance (FTICR) mass spectrometers were adapted to laser microprobe analysis. The instruments with external ion source featured a mass resolution as high as 4 000 000 (for m / z < 100) or at least 100 000 (up to m / z 2000) and a mass accuracy within 10 -6 of the mass-over-charge ( m/z ) ratio. ,, The latter allows the elemental composition of most isobaric ions to be determined individually and thereby specific detection or identification of unknown analytes to be attempted, even in relatively complex mixtures. On the other hand, diffraction limits the minimal spot size to 0.5−1 μm when common refracting optics are used for laser focusing.…”
mentioning
confidence: 99%